Perbandingan Kemampuan Pemahaman Matematis Antara Siswa Yang Mendapatkan Strategi Creative Problem Solving (Cps) Dengan Model Pembelajaran Konvensional: Studi Eksperimen di kelas VII-D dan VII-E SMP Negeri 1 Limbangan - Muliawati, Tina; Sofyan, Deddy (Mosharafa: Jurnal Pendidikan Matematika, 2013)
Most student is passive in the process learning of mathematics that leads to less in their creativity and achievement. Therefore, it needs an effort and innovatively learning of mathematics. As an alternative concerning such things one should develops learning of mathematics with “Creative Problem Solving (CPS)” approach. It is a learning approach which generates an activity between mathematics and students. Thus, it motivates them to solve the problem uniquely with many stagiest. As for which being experiment class is VII-D and VII-E. Class VII-D is getting Creative Problem Solving (CPS) strategy and class VII-E is getting conventional teaching. For the experimental instrument was composed 6 essays. The gain of students' mathematics understanding ability increases getting Creative Problem Solving (CPS) strategy is better than students who received conventional teaching.